2015
DOI: 10.1007/s10863-015-9635-7
|View full text |Cite
|
Sign up to set email alerts
|

MAC inhibitors antagonize the pro-apoptotic effects of tBid and disassemble Bax / Bak oligomers

Abstract: Mitochondrial Apoptotic Channel inhibitors or iMACs are di-bromocarbazole derivatives with anti-apoptotic function which have been tested and validated in several mouse models of brain injury and neurodegeneration. Owing to the increased therapeutic potential of these compounds, we sought to expand our knowledge of their mechanism of action. We investigated the kinetics of MAC inhibition in mitochondria from wild type, Bak, and Bax knockout cell lines using patch clamp electrophysiology, fluorescence microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The intrinsic mitochondrial pathway of apoptosis is an important target for pharmacological manipulation for a variety of diseases including cancer1234567. This pathway is regulated by the BCL-2 family proteins8 and results in the collapse of the inner membrane electrochemical gradient.…”
mentioning
confidence: 99%
“…The intrinsic mitochondrial pathway of apoptosis is an important target for pharmacological manipulation for a variety of diseases including cancer1234567. This pathway is regulated by the BCL-2 family proteins8 and results in the collapse of the inner membrane electrochemical gradient.…”
mentioning
confidence: 99%
“…The release of intramitochondrial contents into the cytosol is considered irreversible during the induction of apoptotic signaling (22). The present study demonstrated that RIPostC, applied as early as possible following reperfusion, may result in a significant neuroprotective effect in the rat MCAO model.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, this group delved further into the exact mechanism of inhibition. 65 When treated with iMAC1 or iMAC2, FL5.12 cells subject to IL-3 deprivation showed a significantly decreased ratio of oligomeric to monomeric Bax compared with control cells. The authors propose that this may be due to disassembly of pre-formed MACs caused by treatment with the inhibitors.…”
Section: Mitochondrial Apoptotic Channel Inhibitorsmentioning
confidence: 93%
“…Peixoto et al reported on mitochondrial apoptotic channel inhibitors (iMACs), 64,65 which are derivatives of dibromocarbazole that have been shown to have antiapoptotic effects in mouse models of neurodegenerative diseases and brain traumatic injury. [66][67][68][69] In 2009, Peixoto et al, demonstrated that iMac2 (2.5 mM and higher) inhibited apoptosis in FL5.12 cells (derived from a murine, pro-B cell line) that were treated with STS or interleukin (IL)-3 deprivation.…”
Section: Mitochondrial Apoptotic Channel Inhibitorsmentioning
confidence: 99%